2020
DOI: 10.1097/aln.0000000000003328
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram Burst-suppression during Cardiopulmonary Bypass in Elderly Patients Mediates Postoperative Delirium

Abstract: Background Intraoperative burst-suppression is associated with postoperative delirium. Whether this association is causal remains unclear. Therefore, the authors investigated whether burst-suppression during cardiopulmonary bypass (CPB) mediates the effects of known delirium risk factors on postoperative delirium. Methods This was a retrospective cohort observational substudy of the Minimizing ICU [intensive care unit] Neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 52 publications
4
65
0
1
Order By: Relevance
“…Therefore, it is a seductive idea that the appearance of this pattern is an indicator of brain pathology and that elderly patients showing intraoperative burst suppression may then go on to develop disrupted cognitive function postoperatively. In this issue of the journal, a study by Pedemonte et al 1 replicates the results from a number of previous observational studies, showing that intraoperative burst suppression was associated with a marked increase (from 6 to 25%) in postoperative delirium after cardiac surgery. From table 1 of their article, 15 of the 20 patients who had postoperative delirium had displayed a burst suppression EEG pattern during their surgery.…”
supporting
confidence: 75%
“…Therefore, it is a seductive idea that the appearance of this pattern is an indicator of brain pathology and that elderly patients showing intraoperative burst suppression may then go on to develop disrupted cognitive function postoperatively. In this issue of the journal, a study by Pedemonte et al 1 replicates the results from a number of previous observational studies, showing that intraoperative burst suppression was associated with a marked increase (from 6 to 25%) in postoperative delirium after cardiac surgery. From table 1 of their article, 15 of the 20 patients who had postoperative delirium had displayed a burst suppression EEG pattern during their surgery.…”
supporting
confidence: 75%
“…40 For example, anesthetic-induced frontal alpha power decreases with age, 37 yet there is still substantial variance in alpha power among older adults. 8 In fact, Hesse and colleagues found that markers of “brain age” can predict postoperative delirium better than chronological age, perhaps due to age-dependent biological changes that occur within the brain. 7 Interestingly, chronological age was not a significant predictor of delirium in this study, which likely reflects the relative narrow age distribution of the cohorts studied here (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[134][135][136][137][138] Known POD risk factors, including limited physical function, lowest body temperature on CPB, and EEG alpha power, may increase the risk of delirium by means of their impact on burst suppression during CPB. 139 Given the relationship between hypotension and neurologic insult during cardiac surgery, some have advocated the use of EEG for monitoring of burst suppression, particularly given the increased postoperative mortality associated with concurrent hypotension and waveform suppression in a recent large RCT (ENGAGES trial), although no difference in POD incidence was noted. [140][141][142] EEG use for neuromonitoring is limited by the cumbersome application of the electrodes, requiring skill to interpret, and its primary function as a monitor of the superficial layers of the cerebral cortex.…”
Section: Unprocessed Eegmentioning
confidence: 99%